Optimalisasi pelayanan apotik panjen di Desa Wedomartani Ngemplak Sleman Yogyakarta - Lutfi Chabib; Akhmad Fauzy (UII, 2020)
Community service activities have been completed to optimize Panjen Pharmacy services. Pharmaceutical services are integrated activities aimed to identify, prevent, and resolve drug problems and health-related problems. The demands of patients and society for improving the quality of pharmaceutical services require the expansion of the old drugs-oriented paradigm into a new patient-oriented paradigm with the philosophy of Pharmaceutical Care. The Panjen Pharmacy in Wedomartani Village, Sleman is still constrained in implementing pharmaceutical services. Based on the results of observations to partners, these problems resulted from A limited number of human resources, lack of facilities and infrastructure, the absence of standardized etiquette, no drug information handbook, and there is no counseling card. The average number of visits by patients who buy drugs at the Panjen Pharmacy per day reaches 35-70 people. So it is necessary to improve services to provide a sense of security to patients about the use of drugs to be consumed. The outcome of this service activity is to optimize Panjen Pharmacy services through increasing human resource capacity, improving infrastructure, availability of standard etiquette, counseling cards, and drug information book achieved with the Participatory Rural Appraisal (PRA) participatory community empowerment model. The continuity of this service activity is the achievement of consistency in the application of a good and correct rationing system, both in terms of Human Resources Utilization (Human Resources), as well as in terms of a management information system that can guarantee the availability of the right type of drug, the right amount, the right quality and the right time. , thus making the pharmacy better in terms of service to the community and healthier.